Viscosity and Density of Chrom Alum in Aqueous Poly (Ethylene Glycol) Solution at Different Temperature - Merza, S. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Density data of  alum chrom in water and in aqueous solution of poly (ethylene glycol) (1500) at different temperatures (288.15, 293.15, 298.15) k have been used to estimate the apparent molar volume (VÎ¸), limiting apparent molar volume (VÎ¸Ëš) experimental slope (Sv) and the second derivative of limiting partial molar volume [Î´2 Î¸ vÂ° /Î´ T2] p .The viscosity data have been analyzed by means of Jones â€“Dole equation to obtain coefficient A, and  Jones â€“ Dole coefficient B, Free activation  energy of activation per mole of solvent, Î”Î¼10* solute, Î”Î¼20* the activation enthalpy Î”H*,and entropy, Î”S*of activation of viscous flow. These results have been discussed in terms of solute â€“solvent interaction and making/breaking ability of solute in the given solution.